2010
DOI: 10.4103/0301-4738.60075
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront analysis and modulation transfer function of three multifocal intraocular lenses

Abstract: Purpose:To evaluate wavefront performance and modulation transfer function (MTF) in the human eye after the implantation of diffractive or refractive multifocal intraocular lenses (IOLs).Materials and Methods:This was a prospective, interventional, comparative, nonrandomized clinical study. Uncorrected distance and near visual acuity, and wavefront analysis including MTF curves (iTrace aberrometer, Tracey Technologies, Houston, TX, USA) were measured in 60 patients after bilateral IOL implantation with 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
(39 reference statements)
2
18
1
4
Order By: Relevance
“…Spherical aberration in eyes with the ZM900 was significantly lower than in eyes with other multifocal IOLs, including both refractive and diffractive multifocal IOLs. 16 Compared to monofocal IOLs, spherical aberration of the ZMA00 was comparable to the TECNIS monofocal IOL and significantly better than spherical monofocal IOLs. 17 Contrast sensitivity improvements following ZM900 implantation were statistically significant across all stimulus spatial frequencies examined.…”
Section: Previous Studies Have Shown That Patientsmentioning
confidence: 96%
“…Spherical aberration in eyes with the ZM900 was significantly lower than in eyes with other multifocal IOLs, including both refractive and diffractive multifocal IOLs. 16 Compared to monofocal IOLs, spherical aberration of the ZMA00 was comparable to the TECNIS monofocal IOL and significantly better than spherical monofocal IOLs. 17 Contrast sensitivity improvements following ZM900 implantation were statistically significant across all stimulus spatial frequencies examined.…”
Section: Previous Studies Have Shown That Patientsmentioning
confidence: 96%
“…This aberrometer was already used in several studies. [24][25][26][27] Furthermore, some studies reported the comparability and repeatability of ray tracing aberrometers with good results. [28][29][30][31][32] However, no previous study measured the aberration of multifocal IOLs using a ray tracing-type aberrometer.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial wavefront sensors assume that this constant provides a smooth, continuous wavefront. 25 Because in theory multifocal IOLs provide 2 emergent wavefronts, it is reasonable to ask which wavefront the aberrometer device actually obtains and measures. As Charman et al 26 discussed, if there is a point source on the patient's retina, as provided for example in a Hartmann-Shack aberrometer, theoretically 2 wavefronts will emerge from the eye; that is, a regular (flat) wavefront produced by the distance correction and a converging spherical wavefront produced by the diffractive near addition.…”
mentioning
confidence: 99%